(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
Preschool age is a critical period for children’s physical, psychological and social development. One of the key components of ensuring full and healthy development is physical activity and sports activities. The preparation of future Bachelors of physical culture for coaching activity in game sports with preschoolers is relevant and important in the context of sports training of children at an early age. This article examines key aspects of this topic and aims to explore the best approaches and methods for training future coaches. In particular, the authors investigate methods of teaching basic motor skills, special techniques and strategies used in game sports. They determine which training approaches are most suitable for young children and contribute to their physical and psychomotor development. This analysis makes it possible to determine the optimal teaching methods and techniques that can be successfully applied when working with preschool children in the context of game sports. The author examines in detail the issue of education and training of preschoolers in the field of game sports, and also pays attention to the adaptation of coaching activities to the individual characteristics of each child of this age. Modern pedagogical and methodical approaches are analyzed, which allow to ensure effective sports training for young athletes. The article also highlights the importance of this topic for the healthy development of children and improving the qualifications of future physical culture coaches. It offers recommendations to improve the training process and promote the development of young athletes on their way to achieving their sporting goals. The practical aspect is also important, namely the introduction of the recommendations and approaches proposed in the article into the educational process. This may require cooperation with educational institutions and training centers to implement new methodological approaches and training programs.